Development And Characterisation Of Biomass-Based Cellulose Hydrogels For Nanoemulsion Drug Delivery To The Skin - Wong, Li Ching (2024)
Cellulose hydrogels with a substantial swelling ability can serve as drug reservoirs for drug delivery to the skin. The potential of solid non-woody biomass (NWB) cellulose hydrogels as a platform for nanoemulsion (NE) drug delivery to the skin remains unexplored. This study aims to develop NWB cellulose hydrogels for dermal delivery of NE by dissolving cellulose from oil palm empty fruit bunch (E) and kapok seed pod (K) fibres in an aqueous alkali solvent system.